PENGARUH KECERDASAN EMOSIONAL DAN KECERDASAN SPRITUAL TERHADAP KINERJA PEGAWAI PADA BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA KABUPATEN KOLAKA TIMUR - Wiguna, Andri Chandra; Kalsum , Ummy; Putera, Asrip (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM Azramedia indonesia, 2024)
This research aims to determine and analyze the impact of emotional intelligence and spiritual intelligence on employee performance at the Office of Human Resources and Empowerment of East Kolaka Regency. The sample consists of all employees at the Office of Human Resources and Empowerment of East Kolaka Regency, totaling 46 individuals. The study utilizes Multiple Linear Regression analysis. The results of the study indicate that: (1) Emotional intelligence and spiritual intelligence have a positive and significant impact on employee performance at the Office of Human Resources and Empowerment of East Kolaka Regency. (2) Emotional intelligence has a positive and significant impact on employee performance at the Office of Human Resources and Empowerment of East Kolaka Regency. (3) Spiritual intelligence has a positive and significant impact on employee performance at the Office of Human Resources and Empowerment of East Kolaka Regency.